Air temperature at 90 km altitude in the Artic obtained using meteor radar : validation, characterization and climate change. - Kluken, Lars Grytbakk (Universitetet i Tromsø, 2011)
Temperatures at 90 km altitude above Ramfjordmoen (69°N, 19°E) have been obtained with the Nippon/Norwegian Tromsø Meteor Radar. The temperatures have been derived from meteor radar decay rates using two techniques: the pressure based and the temperature gradient based methods. The results have been compared to the Microwave Limb Sounder (MLS) instrument on board the Aura spacecraft. It was found that the pressure method was simpler to implement than the temperature gradient method and gave better results in relation to the MLS temperatures. With the use of a technique for statistical comparison of geophysical data, the intrinsic uncertainty of the radar temperatures was estimated to be less than 4 K. Two attempts to combine the two techniques in order to measure both temperatures and pressure with the meteor radar have been carried out. One of the approaches proved to be feasible and gave promising results. This indicates that the meteor radar may have the potential of producing continuous temperature and pressure measurements virtually independent of external data. A new collocated sodium lidar is introduced and some initial comparisons are carried out between the two instruments. At times there were large discrepancies, but more data is necessary in order to obtain reliable results. Finally, some possible uses of the radar temperatures are proposed. A method for investigating long term trends is discussed in detail. The data available resulted in a trend of - 2.2 K per decade, but more data is required to establish a trend with higher confidence. It was estimated that approximately 13 years of data are needed to determine the trend with a probability of 90 %.